Analisis Pengaruh Migrasi kWh Meter Pascabayar Menjadi Prabayar Terhadap Susut Non Teknis pada PT PLN (Persero) ULP Kota Fajar - Aziz, Novfan Maghresa; Tarigan, Adisastra Pengalaman; Rahmaniar, Rahmaniar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Electric energy has crucial role in today's life. In its usage, the kWh meter holds significant importance in measuring electricity consumption, aiming to secure revenue from the company's perspective. PT PLN (Persero), as the primary provider of electricity, uses kWh meters as a medium for transactions with consumers. PT PLN (Persero)'s revenue is derived from the sale of electricity delivered to consumers, as measured by kWh meters. Therefore, it is essential that the measurement of consumer electricity consumption through the kWh meter is accurate, ensuring no energy is unaccounted for. To achieve accurate measurements, monitoring and evaluation of field implementation and the equipment used are necessary. If not carried out properly, it may lead to losses in the form of non-technical losses, which could occur due to electricity theft or damaged or malfunctioning kWh meters owned by customers. The replacement of faulty kWh meters aims to avoid errors in measuring electricity consumption, which could affect the billing of electricity usage payments.